2023
DOI: 10.1109/jbhi.2023.3311628
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning in Surgical Workflow Analysis: A Review of Phase and Step Recognition

Kubilay Can Demir,
Hannah Schieber,
Tobias Weise
et al.

Abstract: In the last two decades, there has been a growing interest in exploring surgical procedures with statistical models to analyze operations at different semantic levels. This information is necessary for developing context-aware intelligent systems, which can assist the physicians during operations, evaluate procedures afterward or help the management team to effectively utilize the operating room. The objective is to extract reliable patterns from surgical data for the robust estimation of surgical activities p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…Technologies that enable next-generation context-aware systems in the operating room are currently intensively researched in the domain of surgical workflow recognition [ 1 ]. Recent studies that apply machine learning algorithms to this task have shown highly promising results [ 2 , 3 ]. To further support advances in this area, academic machine learning competitions are hosted regularly [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Technologies that enable next-generation context-aware systems in the operating room are currently intensively researched in the domain of surgical workflow recognition [ 1 ]. Recent studies that apply machine learning algorithms to this task have shown highly promising results [ 2 , 3 ]. To further support advances in this area, academic machine learning competitions are hosted regularly [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%